Comments on the geochemistry of rare-earth elements (La, Ce, Sm, Eu, Tb, Yb, Lu) with examples from coals of north Asia (Siberia, Russian far East, North China, Mongolia, and Kazakhstan); International Journal of Coal Geology; Vol. 206 - Arbuzov S. I. Sergey Ivanovich; Chekryzhov I. Y.; Finkelman R. B. Robert Barry; Sun Yuzhuang; Zhao Cunliang; Iljenok (Il'enok) S. S. Sergey Sergeevich; Blokhin M. G. Maksim Gennadjevich; Zarubina N. V. (2019, 2019)
Title screen